Torrential floods in Malaysia: assessing the loss and vulnerabilities in three Kelantan villages - Karim, A.H.M Zehadul; Md. Noon, Hazizan; Mohamad Diah, Nurazzura; Tajuddin, Nor Azlin (2016)
This research is an attempt to explore the socio-economic loss and vulnerabilities of the people in three villages of Kelantan State who have been considered as the worst victims of the calamity in December 2014 Flood in Malaysia. Three villages named, Kg.Laloh, Kg Manjor and Kg Manik Urai Lama were chosen purposively which later were surveyed most extensively to make the study totally enumerated in nature. As part of the qualitative study, the research conducted three FGDs and 10 in-depth interviews. Findings of the study indicate that with a few exceptions, the great majority of the villagers regardless of their socio-demographic position, suffered badly from the floods in terms of losing their shelter, food, pure drinking water and having non-availability of transport and carrier for immediate shiftment. In addition to these vulnerabilities, villagers having farming or/ and farming related activities also endured badly as many of them lost their crops and animals during the flood. Based on the above, the research suggested that the government or policy planners consider building shelter houses in strategic locations of the villages immediately to protect the life of the people during the flood upsurge in future and thus reduce their vulnerabilities. It is advisable that a community resilience and preparedness should be well articulated in advance with the involvement of the local people. There should be a proper coordination in providing aids to the people during the flood so that all the victims receive them equally to mitigate their economic crises and sufferings.